Pore-water pressure and water volume change of an unsaturated soil under infiltration conditions - Meilani, Inge (2011)
Triaxial shearing infiltration tests were conducted to study the pore-water pressure and volume change of unsaturated soils subjected to infiltration conditions. A modified triaxial apparatus with three Nanyang Technological University (NTU) mini suction probes along the specimen height was used for the experimental program. Elastic moduli were obtained for the soil structure with respect to changes in net confining pressure (E) and matric suction (H). Water volumetric moduli associated with changes in net confining pressure (Ew) and matric suction (Hw) were also obtained from the shearing infiltration tests. Water volumetric strain and pore-water pressure during the shearing infiltration tests were computed based on volume change theory. This paper presents the significance of obtaining the parameter Hw from an appropriate scanning curve of a soil-water characteristic curve (SWCC) for the computation of water volumetric strain and pore-water pressure changes during a shearing infiltration test. The appropriate scanning curve should be obtained from the wetting curve of the SWCC at the matric suction where the infiltration test commences.